Measuring trust: an experiment in Brazil - Sergio G. Lazzarini; Regina Madalozzo; Rinaldo Artes; José de Oliveira Siqueira (Economia Aplicada, 2005)
Attitudinal measures of trust, such as those employed by the World Values Survey (WVS) or the General Social Survey (GSS), have been shown to be correlated with important country-level variables reflecting economic and institutional development. However, Glaeser, Laibson, Scheinkman and Soutter (Quarterly Journal of Economics, 2000) have found that those attitudinal measures poorly correlate with behavioral measures of trust obtained from an experimental "trust game" involving monetary incentives. We replicate Glaeser's et al. study using Brazilian subjects and performing the experiment under two conditions: when individuals meet face-to-face prior to their interaction, and when they cannot do so. We find that the effect of attitudinal measures of trust (such as the WVS/GSS scale) on subjects' trusting behavior in experimental transactions appears to be significantly larger when they cannot meet face-to-face (a condition that was not employed in Glaeser's et al. study). Echoing Glaeser's et al. results, we also find that attitudinal measures of trust are significantly correlated with rustworthy behavior: individuals who affirm to be more trusting are apparently less inclined to act opportunistically. Thus, evaluating attitudinal measures of trust within appropriate experimental conditions, we find that measures such as the WVS/GSS scale appear to have a role in explaining both trusting and trustworthy behavior.